2003
DOI: 10.1002/pbc.10368
|View full text |Cite
|
Sign up to set email alerts
|

Serum troponin T levels and echocardiographic evaluation in children treated with doxorubicin

Abstract: No correlation was found between serum cTnT values, cumulative doxorubicin doses, and systolic or diastolic cardiac functions. We can conclude that echocardiographic follow-up is more reliable than serum cTnT levels for detecting subclinical cardiac toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 19 publications
0
49
0
Order By: Relevance
“…The clinical value of cTn and NPs measurement in diagnosis of heart failure during and after the anticancer treatment has been evaluated in several studies with adults and children [7,9,13,14,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical value of cTn and NPs measurement in diagnosis of heart failure during and after the anticancer treatment has been evaluated in several studies with adults and children [7,9,13,14,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Currently there is no optimal method that can be used for early detection of subclinical late cardiotoxicity. The role of biochemical cardiomarkers that reflect cardiomyocyte degeneration (serum levels of cTnT) and functional myocardial changes (serum levels of NT-proBNP) in early detection of cardiotoxicity of cytostatics have been evaluated in many clinical and experimental studies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an increase in Tn-I was associated with a 17.6 times increased risk of cardiotoxicity, and emerged as the only independent predictor of lack of recovery in LVEF despite treatment with HF therapy, which consisted of enalapril and carvedilol upbeing titrated to maximally tolerated doses used in conventional HF [48]. However, these results still need to be confirmed [49][50][51]. High-sensitive troponins assays may have a greater interest for the detection of subclinical myocardial damage.…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…They proposed that determining serum levels of cTnT is a sensitive means for assessing the early cardiotoxicity of DOX. 33 However, Kismet et al 34 found no correlation between serum cTnT levels and cumulative DOX levels in 24 patients treated with DOX. In addition, they showed no correlation between serum cTnT levels and ECHO detected systolic and diastolic findings.…”
Section: Duxorubicinmentioning
confidence: 99%
“…Generally speaking, cardiotoxicity with cumulative doses above 450 mg/m 2 is a well-known adverse effect of DOX. 34 Lipshultz et al reported no elevation of serum cTnT levels after discontinuation of anthracycline therapy, but the cumulative DOX doses of their patients were below 222 mg/m 2 and the number of the patients was very few. They found a low level serum cTnT elevations in patients continuing their DOX therapies and suggested that these low-level elevations may persist for a time as an indicator of chronic inflammatory changes.…”
Section: Duxorubicinmentioning
confidence: 99%